Analisis Penataan Arsip Dinamis Inaktif dalam Mendukung Temu Kembali Arsip - Dzaky Tama Maulana; RizaAji Sulton Adila; Diana Eka Poernamawati (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
The arrangement of inactive dynamic records is an important part of records management because it is related to storage organization and the ease of records retrieval. Inactive dynamic records are records whose frequency of use has decreased but still possess functional value, therefore they must be managed systematically. This study aims to analyze the arrangement of inactive dynamic records in supporting records retrieval. The study used a descriptive method with a library research approach. Data were collected through literature studies from books, scientific journals, and relevant regulations. Data analysis was conducted descriptively through data reduction, data presentation, and conclusion drawing. The results showed that systematic records arrangement through records classification, records retention schedules, storage systems, and retrieval aids can improve the effectiveness of records retrieval. The success of records retrieval is influenced by the storage system, the competence of human resources, and the availability of archival facilities and infrastructure. Therefore, proper management of inactive dynamic records plays an important role in supporting the effectiveness and efficiency of records management within an organization.